A Timely Intervention: Endoscopic Retrieval of a Swallowed Magnetized Activity Watch - Jason S. Radowsky; Joseph S. Lee; Andrew T. Schlussel (Case Reports in Gastrointestinal Medicine)
The accidental ingestion of a foreign object often presents a difficult scenario for the clinician. This includes not only the decision to retrieve the material but also the appropriate technique to use. We present the case of a young asymptomatic girl who swallowed a magnetic activity watch, which was then successfully retrieved with an endoscopic snare. To our knowledge, this is the first documented case of salvaging an operational watch from the stomach using an endoscopic technique.